Pengaruh Utilitarian Value, Hedonic Value, dan Social Value terhadap Continuance Purchase Intention Dimediasi Trust in Streamer pada Live Streaming TikTok Shop - Shaadiqiin, Muhammad; Sari, Astri Yuza (Al-DYAS, 2025)
This study aims to analyze the influence of Utilitarian Value, Hedonic Value, and Social Value on Continuance Purchase Intention mediated by Trust in Streamer on TikTok Shop Live Streaming. The population in this study consists of TikTok Shop app users who have made purchases through the TikTok Shop app. The sampling technique used in this research is purposive sampling. The sample size for this study is 132 respondents. Data was collected through the online distribution of questionnaires and processed using SmartPLS software. The results of this study indicate that (1) Utilitarian Value positively influences Trust in Streamer on TikTok Shop Live Streaming. (2) Hedonic Value positively influences Trust in Streamer on TikTok Shop Live Streaming. (3) Social Value positively influences Trust in Streamer on TikTok Shop Live Streaming. (4) Trust in Streamer positively influences Continuance Purchase Intention on TikTok Shop Live Streaming. (5) Utilitarian Value positively influences Continuance Purchase Intention mediated by Trust in Streamer on TikTok Shop Live Streaming. (6) Hedonic Value positively influences Continuance Purchase Intention mediated by Trust in Streamer on TikTok Shop Live Streaming. (7) Social Value positively influences Continuance Purchase Intention mediated by Trust in Streamer on TikTok Shop Live Streaming.